The Effect of Work Motivation and Work Discipline on Employee Performance at the Regional Financial and Asset Management Agency - Astuti, Any; Alam, Iskandar Ali (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study examined the impact of work motivation and discipline on employee performance at the Regional Financial and Asset Management Agency (BPKAD) of Mesuji Regency, Indonesia. It addressed the discrepancy between receiving an unqualified audit opinion for four years and an "adequate" rating in the Government Agency Performance Accountability System (SAKIP), indicating challenges in employee performance beyond financial accountability. A quantitative explanatory design was used, with structured Likert-scale questionnaires administered to all 45 employees of the BPKAD in Mesuji Regency. Multiple linear regression analysis assessed the effects of work motivation and discipline on employee performance. The findings showed that both work motivation and discipline had a positive and statistically significant impact on employee performance. Together, these factors significantly enhanced performance, highlighting the complementary roles of psychological (motivation) and behavioral (discipline) factors in public financial management. The study concluded that improving motivation and enforcing discipline are crucial for enhancing employee performance and improving SAKIP outcomes. A balanced approach involving both intrinsic and extrinsic motivation, along with adherence to work standards, is necessary for better performance. The limitations of this study include its cross-sectional design, small sample size, and reliance on self-reported data. This study contributes to the public sector human resource management literature by integrating motivation and discipline to enhance performance.